La expresión de los recuerdos: el impacto de influencias musicales y emocionales a través de un proceso creativo musical. - Niño Guio, Paula Natalia (Universidad Antonio Nariño, 2025)
This is a research work that seeks understanding about the way the creative processes happen and develops the artistic mind. Because of the limited information on those processes, looking for sources that support the relevance of those issues was necessary, sources that enlighten the possible procedures at the creation time.